Virtual worlds in higher education: a policy simulation. (1st September 2010) - Garcia-Murillo, Martha; MacInnes, Ian; Rubleske, Joe
The purpose of this paper is to explore whether virtual worlds can provide a setting for a rewarding learning experience for college students. The paper describes a policy-making simulation conducted within a virtual world and the results of an analysis conducted to assess its learning effectiveness. Our analysis, drawn from eight 'learning principles' advanced by Gee (2003), indicates that the levels of enthusiasm and learning that take place within a virtual world can differ considerably for different students: while some prefer traditional online methods, others are more enthusiastic about virtual world settings. Of the eight principles we considered, we found evidence to support 'identity and self knowledge', 'active learning', 'psychological moratorium' and 'content' principles. The 'affinity', 'transfer' and 'exploration' principles were not as well supported. In conclusion, we recommend that instructors give serious consideration to using virtual worlds as a tool to support interactive activities of students such as simulations.